KAJIAN RISIKO CEDERA DAN MASALAH UMUM PENDAKI MAHASISWA UNIVERSITAS UDAYANA - Mohamad Izam Zahary (DiscoverSys Inc., 2015)
There are many tourist activities that can be promoted in rural spaces, including the active experience of nature through outdoor sports, either challenging or, rather, calm and contemplative in nature and hiking is one of the most popular forms of enjoying an active nature experience. Highâ€altitude illness may be divided into the acute syndromes that affect lowland or highland residents ascending to altitudes greater than those to which they are accustomed and the chronic conditions that affect individual resident at high altitude for long periods. The acute adult syndromes of high altitude are acute mountain sickness, highâ€ altitude pulmonary oedema (HAPE) and highâ€altitude cerebral oedema. Hypoxia is the main factor for theacute highâ€altitude illnesses. The incidence and severity of acute mountain sickness, HAPE and highâ€altitude cerebral oedema are related to the speed of ascent and the maximum height gained.